Pengaruh Penerapan Model Project Citizen terhadap Peningkatan Civic Disposition Siswa Kelas XI SMA Negeri 7 Binjai - Manik, Khatherine Sesilia; Dharma, Surya (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The purpose of this study was to determine how the application of the Project Citizen learning model affects the Civic Disposition of class XI students of SMA Negeri 7 Binjai. The research methodology used is quantitative. To determine the causal relationship between the independent variable (Project Citizen, variable X) and the dependent variable (Civic Disposition, variable Y), the research design used is a quasi-experiment with a nonequivalent control group design. This research uses data collection techniques, namely questionnaires, documentation studies and observation. This research was conducted at SMA Negeri 7 Binjai North Sumatra. The population in this study were all 11th grade students of SMA Negeri 7 Binjai. While the samples are students of class XI-7 and XI-6. The data found were analyzed statistically with the t test then normality test, homogeneity test and hypothesis testing with paired sample t-test. The results showed that the Project Citizen learning model had a significant effect on improving the Civic Disposition of students in class XI-7. This can be seen from the mean or average results of Pre-Test and Post-Test Civic Disposition in experimental classes. Where the experimental Pre-Test was 100.06 and increased by 15.79, namely the Post-Test result of 115.85. While the Pre-Test in the control class amounted to 102.16 and increased by 6.19, namely the Post-Test result of 108.35. Then the t test results show that the sig. (2tailed) value is 0.000 <0.05, then H_o is rejected then H_aadmitted. Thus it can be concluded that there is a significant effect of applying the citizen project model on increasing the Civic Disposition of students XI-7 SMA Negeri 7 Binjai.